The Effectiveness of Nineteen's RAPCOV Screening Education Through Character Health Communication on Knowledge of Covid-19 Infection - Siti Noorbaya; Dwi Riyan Ariestantia; Fauziah Fauziah (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2021)
The study